Heat transfer characteristics of nanofluids - Sohel Murshed, S. M. (2008)
This thesis reports experimental and theoretical investigations on the thermophysical properties of nanofluids. Experimental results on effective thermal conductivity, effective thermal diffusivity, viscosity and electrokinetic properties of nanofluids are presented and analysed. Two improved theoretical models have been introduced to predict the enhanced thermal conductivity of nanofluids containing spherical and cylindrical nanoparticles. A new double hot-wire technique is also developed for measuring the effective thermal diffusivity of nanofluids.